Dry Land Entisol Chemical Properties and Pak Choi Response Upon Application of Tofu Waste LOF and Biochar - Natalia Desy Djata Ndua; Deseriana Bria (Jurnal Ilmu Pertanian Indonesia, 2025)
This study aimed to examine the changes in the chemical properties of dryland Entisols upon the application of liquid organic fertilizer (LOF) from tofu waste and biochar, especially the content of C-organic, total N, total P, and P2O5 (available P), and the yield of pak choi. This study used a completely randomized factorial design. The first factor was the dose of tofu waste LOF (100, 200, and 300 ml/L water) and the second factor was the type of biochar (soil+rice husk biochar, soil+sawdust biochar, soil+rice husk biochar+ sawdust biochar). The combination of tofu waste LOF (100 ml/L) and the mixture of rice husk biochar and sawdust biochar (1:1:1) resulted in the most significant increase in C-organic (7.37%), total N (0.61%), total P (178.01 mg/100 g), and P2O5 (157.23 ppm) compared to other treatments. However, at a high dose of tofu waste LOF (300 ml/L of water), the contents of C-organic, total N, total P, and P2O5 tended to decrease, presumably due to the low pH of the tofu waste LOF. In terms of plant parameters, rice husk biochar treatment was the best for increasing the fresh weight of the shoots. This indicates that the optimal combination of LOF and biochar improved the chemical properties of Entisol analyzed after harvesting but did not increase the yield of pak choi at the beginning of application. However, rice husk biochar alone provided the best results for pak choi as an indicator plant. Keywords: C-organic, nitrogen, phosphorus, soil fertility, Timor